Women's Work, Markets and Economic Development in Nineteenth-Century Ontario - Cohen, Marjorie Griffin, 1944- (Book collections on Project MUSE., 1988)
Cohen focuses on the productive relations in the family and the significance of women's labour to the process of capital accumulation in both the capitalist sphere and independent commodity production.